2010
DOI: 10.1016/j.psyneuen.2009.07.010
|View full text |Cite
|
Sign up to set email alerts
|

High pregnancy anxiety during mid-gestation is associated with decreased gray matter density in 6–9-year-old children

Abstract: Summary Because the brain undergoes dramatic changes during fetal development it is vulnerable to environmental insults. There is evidence that maternal stress and anxiety during pregnancy influences birth outcome but there are no studies that have evaluated the influence of stress during human pregnancy on brain morphology. In the current prospective longitudinal study we included 35 women for whom serial data on pregnancy anxiety was available at 19 (±0.83), 25 (±0.9) and 31 (±0.9) weeks gestation. When the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
274
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 381 publications
(298 citation statements)
references
References 129 publications
13
274
0
11
Order By: Relevance
“…Neuroimaging studies have primarily focused on changes in limbic structures responsive to stress and critical for emotion, including the prefrontal cortex and hippocampus. For instance, prenatal anxiety was reported to associate with offsprings' gray matter volume reductions in the prefrontal cortex at 6-9 years of age (Buss et al, 2010). A separate study similarly observed an effect of prenatal maternal anxiety on neonatal frontal cortical thickness that was moderated by functional variants of the catechol-O-methyltransferase (COMT) gene, which regulates catecholamine signaling and is implicated in anxiety, pain, and stress responsivity (Qiu et al, 2014).…”
Section: Neuroanatomicalmentioning
confidence: 98%
“…Neuroimaging studies have primarily focused on changes in limbic structures responsive to stress and critical for emotion, including the prefrontal cortex and hippocampus. For instance, prenatal anxiety was reported to associate with offsprings' gray matter volume reductions in the prefrontal cortex at 6-9 years of age (Buss et al, 2010). A separate study similarly observed an effect of prenatal maternal anxiety on neonatal frontal cortical thickness that was moderated by functional variants of the catechol-O-methyltransferase (COMT) gene, which regulates catecholamine signaling and is implicated in anxiety, pain, and stress responsivity (Qiu et al, 2014).…”
Section: Neuroanatomicalmentioning
confidence: 98%
“…Developmental trajectories in the brain are strongly altered by prenatal stress or high pregnancy anxiety, which leads to grey matter volume reductions in several brain areas (prefrontal cortex (PFC), hippocampus and hypothalamus) in humans 90,91 and rodents [92][93][94] . Rodent studies suggest an important role for glucocorticoid-induced apoptosis in some of these effects 95 .…”
Section: Structural Changesmentioning
confidence: 99%
“…A wealth of studies have shown that offspring of mothers with high levels of psychosocial stress, depression or anxiety are at increased risk for adverse neurodevelopmental outcomes, showing more internalizing and externalizing behavior problems (O'Connor et al 2002;O'Connor et al 2003;O'Donnell et al 2014) higher symptoms of depression (Pawlby et al 2009;Pearson et at 2013;Plant et al 2013) and alterations in biological systems such as brain morphology (Buss et al 2010) and epigenetic profiles (Oberlander et al 2016). Higher levels of cortisol during pregnancy have also been related to offspring IQ (LeWinn et al 2009), behavior and temperament (de Weerth et al 2013).…”
Section: Introductionmentioning
confidence: 99%